Pengaruh Penggunaan Lkpd Dan Media Video Berbasis Youtube Materi Pecahan Terhadap Kemampuan HOTS Siswa SDN 04 Palembang - Putri, S; Misdalina; Abdullah, BZ Septeiyawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low ability of Higher Order Thinking Skills (HOTS) of students in mathematics, especially fractions. This study aims to determine the effect of the use of LKPD and YouTube-based video media on HOTS abilities of second-grade students of SDN 04 Palembang. The research method used is quantitative with a Post-test Only Control Group Design. The population in this study were all second-grade students of SDN 04 Palembang, totaling 89 people, with a research sample of 58 people divided equally into the experimental group (n = 29) and the control group (n = 29). The data analysis technique used the swimmer test, namely the Shapiro-Wilk normality test, Levene's homogeneity test, and continued with hypothesis testing using the Independent Sample t-test. The results showed that the use of LKPD combined with YouTube-based video media had a significant effect on improving students' HOTS abilities in fraction material. This is evidenced by a significance value (2-tailed) of 0.000 <0.05 and a t-value of 7.690. The experimental group achieved an average score of 76, while the control group achieved a score of 52. The conclusion of this study is that YouTube-based video media and student worksheets (LKPD) are effective when used together as learning tools to develop higher-order thinking skills in elementary school students.